Evaluation of master’s project course learning Outcomes at Open University of Malaysia - Hazalina Hashim,; Sharifah Rosfashida Syed Abd Latif , (ASEAN Journal of Open and Distance Learning, 2019)
Learning outcomes are statements on what learners should know, understand and be able to do upon successful completion of a course. Achievement of learning outcomes is an important criterion for a programme to be accredited by the Malaysian Qualifications Agency. Evidence from teaching and learning evaluation needs to demonstrate that the learning outcomes have been achieved. The purpose of this study is to evaluate the learning outcomes of a final year master’s project according to the course learning outcomes and learning domains determined by the Malaysian Qualifications Agency. This evaluation is carried out by analysing the feedback provided by supervisors and learners. The survey which was administered for postgraduate learners in the academic session of 2018, measured to what extent the completion of the course met the learning outcomes and fulfilled the learning domain skills stipulated. To strengthen the evidence, the results obtained from the master’s project report awarded by supervisors and reviewers were compared according to chapters, programme and learning outcomes. The findings were discussed to highlight concerns, strengths and weaknesses based on the evaluation. Several recommendations for continuous improvement and support were proposed to improve the quality of the course and achievement of the learning outcomes. [ABSTRACT FROM AUTHORS]